Kategorialnost leksemov med slovarjem in slovnico - Vidovič-Muha, Ada (Slavistična revija, 2006)
The present article builds on the understanding of interwinement of lexical and grammatical linguistic issues - of the paradigmatic and syntagmatic aspects of lexico-semantic analysis. The categorial semantic features as definitional properties of individual sentence elements divide lexemes into those which concretize these categorial semantic features when performing syntactic functions and tjhose which do not. A change in the syntactic function of the lexeme results in the change of categorial semantic features and, consenquently, in the change of the lexical meaning. It is characteristic of lexemes with syntactic functions that their denotata are part of the propositional structure of the (under lying) sentence meaning if these are verbs or nouns or adverbs of exterior circumstances. Outside the proposition remain the semantic "modificators" of propositional lexemes, the adjective next to noun, and the adverb of interior circumstances next to the verb. The meaning of the lexemes with such denotata can be represented structurally as a hierarchically organized string of semantic features which reflect the logical relationship between what it conceptually wider and conceptually narrower.
Keywords: besedotvorje; grammar; leksemi; leksikografija; lexicography; semantics; semantika; Slovene; slovenščina; slovnica; word formation